A tragédia em Tolkien: uma análise literária sobre a presença do trágico em Os filhos de Húrin - Salesse, Alinne Pavani [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
J.R.R. Tolkien was a philologist, professor and writer who revolutionized the literary world with his books. Gifted with imagination, added to the knowledge he had about myths and linguistics, he was able to create and describe a Universe dissimilar to everything that existed before. This course's final paper aims to analyze the presence of Tragycal characteristics at the novel The Children of Húrin (Narn I Chîn Húrin), written by Tolkien. Unlike the most stories written by the Professor, the outcome of the plot reveals the sad path of Túrin Turambar, a brave man with a bad temper who lived back in the so called Early Days, at the Second Age of Middle-Earth. Described for the first time in the pages of The Silmarillion, the tale about the children of Húrin gathers characters of many species, diversifying between brave warriors and mystic creatures. The presence of the supernatural and the contest between good and evil forces are found in the book as well. The present paper work aims to feature the events of Túrin's life, as well as his behaviour, as examples of tragycal elements which can be found in tales and several other kinds of art since the rise of the Tragedy in a long time before Tolkien

J.R.R. Tolkien foi um filólogo, professor e escritor que revolucionou o mundo literário com suas obras. Dotado de criatividade e auxiliado pelo conhecimento que tinha sobre mitos e linguística, foi capaz de imaginar e descrever um Universo diferente de tudo o que existira até então. Esse Trabalho de Conclusão de Curso pretende analisar a presença de características derivadas da Tragédia no romance Os Filhos de Húrin (Narn I Chîn Húrin), escrito por Tolkien. Diferindo da maioria das histórias do Professor, o desfecho da obra estudada apresenta a triste trajetória de Túrin Turambar, homem valente e de temperamento difícil que viveu durante os Dias Ancestrais, na Primeira Era da Terra-Média. Descrito pela primeira vez nas páginas da obra O Silmarillion, o conto sobre os filhos de Húrin reúne personagens de várias espécies, variando entre bravos guerreiros e criaturas místicas. A presença do sobrenatural e a batalha entre forças do bem e do mal, também constam no livro. O presente trabalho visa caracterizar os acontecimentos da vida e do comportamento de Túrin como exemplos de elementos fundamentalmente trágicos, que são encontrados em narrativas e diversas formas de arte desde o surgimento da Tragédia, em tempos remotos à época de Tolkien
Keywords: Tolkien, J. R. R John Ronald Reuel 1892-1973 Os filhos de Húrin; Literatura; Critica; Tragedia; Tragedy